(untitled) (Bulletin KNOB, 1996)
The government-architect Gijsbert Friedhoff (1892-1970) left an important mark on the architecture of the Dutch state after World War II, when large parts of The Netherlands had to be rebuilt. The works of this period, known as the post-war reconstruction architecture (1946-1965), are at the moment seriously threatened by developments in building and city planning. The crucial problem is that most of the post-war reconstruction architecture is too young to be protected by the Historic Buildings and Ancient Monuments Act 1988, which applies a terminus ante quem of minimal 50 years. This means that during the next decennium buildings of a high quality Standard in architecture, siting and decoration inevitably will disappear, unless cities and provinces will take their responsibility by making their own rules for the keeping of valuable specimens of postwar architecture and city planning. The works of Friedhoff are a touchstone in this process. His former offices for the ministry of Education, Arts and Sciences (Onderwijs, Kunsten en Wetenschappen) (1953) in the Hague are being demolished at this very moment, whereas in Oostburg (Zeeland) his District-court (Kantongerecht) (1953) is threatened by plans of the very municipality that once requested the central government to build it. The council of Oostburg wants to use the spot to construct a mall. This is all the more regrettable because of the great quality of Friedhoff’s designs. Raised in the tradition of the Delft school (Delftse school) Friedhoff combined a solid craftmanship with traditional motifs to suggest dignity and decorum, which his tutor, professor Henri Evers characterised as ’the morality of a building’. His buildings are expressive by the grouping of masses as well as lucid by their ground plan, in which he tried to accomplish a ’climax’ by the sequence and the form of the various spaces. His idea was to set an example for state-architecture, which appealed to the public by expressing the values of the community and the government. Friedhoff was able to carry out this programm to its full extent by calling in the assistance of interior decorators and designers of furniture, sculpture, armatures, glass-stained-windows, graffiti, mosaics and murals. In this he proved to be a true heir of the Dutch tradition of Cuypers and Berlage, who also created an appealing impression in their buildings by exploiting the visual and symbolic possibilities of architectural elements in combination with the decorative and applied arts. Both the in- and exterior of a building contained in their view a message in stone. One can only hope that the call of tradition will reach politicians and administrators in time to create new chances for the post-war reconstruction. ’I struggle and overcome’ is the device of the coat of arms of the province of Zeeland, and refers to its ever-continuous struggle with the sea.